Systematic review: chronic obstructive pulmonary disease and work-related outcomes. (8th March 2018) - Rai, K K; Adab, P; Ayres, J G; Jordan, R E
Abstract: Background: Several studies have assessed the impact of chronic obstructive pulmonary disease (COPD) on work ability and work productivity; however, this relationship is poorly understood. Aims: To undertake a systematic review to assess the effects of COPD on employment, absenteeism and presenteeism. Methods: A comprehensive search using CINAHL, Embase, MEDLINE and the Cochrane Library was conducted to include epidemiological studies from 1937 to August 2017. One reviewer screened all citations. Shortlisted full-text articles were independently assessed by a second reviewer. Data were extracted by one reviewer with a random sample of papers (45%) checked by a second reviewer. Results: Forty-four studies were included; the majority of evidence was from cross-sectional studies, and some cohort studies. COPD patients had lower employment rates than those without COPD. Among those in work, most studies showed patients with COPD took more time off work than those without and reported poorer work performance (presenteeism), although evidence for this association was weaker. The influence of disease severity on these outcomes was unclear; however, it appeared that increasing severity of airflow obstruction was associated with reduced likelihood of being employed. A number of methodological limitations were found among the evidence, including the lack of adjustment for important confounders. Conclusions: Future studies are required which assess the impact of COPD on presenteeism using validated presenteeism instruments and consistent reporting methods. Robust studies are now needed to identify modifiable factors associated with these poorer working outcomes to inform future interventions aimed at improving work productivity among those with COPD.